2023
DOI: 10.1186/s43168-023-00189-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term evaluation of motor and sensory nerve conduction parameters in COVID-19-associated peripheral neuropathy patients

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS‐COV‐2) is mostly associated with upper and lower respiratory tract manifestations. However, coronavirus disease 19 (COVID-19) can result in a wide range of other systemic symptomatology, including neuropsychiatric, psychological, and psychosocial impairments. Literature regarding neurological compromise, including neuropathy and sensory and motor affection associated with COVID-19, is still limited. This study aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…I am writing this letter in response to the letter to the editor submitted to the Egyptian Journal of Bronchology with an inquiry on my recently published paper in your reputable journal under the title “Short-term Evaluation of motor and sensory nerve conduction parameters in COVID-19-associated peripheral neuropathy patients” [ 1 ].…”
mentioning
confidence: 99%
“…I am writing this letter in response to the letter to the editor submitted to the Egyptian Journal of Bronchology with an inquiry on my recently published paper in your reputable journal under the title “Short-term Evaluation of motor and sensory nerve conduction parameters in COVID-19-associated peripheral neuropathy patients” [ 1 ].…”
mentioning
confidence: 99%
“…On using motor and nerve conduction studies, Shaddad et al [ 1 ] found that motor nerve conduction (MNC) latency and amplitude for the median nerve (MN) were deranged significantly in COVID-19 patients. The COVID-19 patients also had significantly greater MNC latency and F wave latency for the posterior tibial nerve (PTN).…”
mentioning
confidence: 99%
“…The COVID-19 patients also had significantly greater MNC latency and F wave latency for the posterior tibial nerve (PTN). The D-dimer and C-reactive protein levels were correlated with a significant positive association with a latency of MN MNC, sensory nerve conduction (SNC), and f-wave; latency of MNC and F wave of the PTN; and SNC latency for sural nerve [ 1 ]. In addition to the study limitation of the lack of long-term follow-up which was addressed by Shaddad et al [ 1 ], we, hereby, explore the following limitation.…”
mentioning
confidence: 99%
See 2 more Smart Citations